2021
DOI: 10.1073/pnas.2102435118
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of elastase enhances the adjuvanticity of alum and promotes anti–SARS-CoV-2 systemic and mucosal immunity

Abstract: Alum, used as an adjuvant in injected vaccines, promotes T helper 2 (Th2) and serum antibody (Ab) responses. However, it fails to induce secretory immunoglobulin (Ig) A (SIgA) in mucosal tissues and is poor in inducing Th1 and cell-mediated immunity. Alum stimulates interleukin 1 (IL-1) and the recruitment of myeloid cells, including neutrophils. We investigated whether neutrophil elastase regulates the adjuvanticity of alum, and whether a strategy targeting neutrophil elastase could improve responses to injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
(82 reference statements)
0
23
0
2
Order By: Relevance
“…The copyright holder for this preprint this version posted December 9, 2021. ; https://doi.org/10.1101/2021.12.07.471590 doi: bioRxiv preprint antibody function by U-Omp19 addition to formulations could also be due to its protease inhibitor activity. U-Omp19 can inhibit neutrophil elastase 18 and Kim et al have recently shown that coadministration of a neutrophil elastase inhibitor enhances the affinity and function of antibodies induced by alum as adjuvant 55 . In the same work, Kim et al showed that neutrophil elastase inhibitor supplementation can improve the efficacy of alum-adsorbed anti-SARS-CoV-2 vaccines by promoting the induction of IgA in the serum and mucosal secretions 55 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted December 9, 2021. ; https://doi.org/10.1101/2021.12.07.471590 doi: bioRxiv preprint antibody function by U-Omp19 addition to formulations could also be due to its protease inhibitor activity. U-Omp19 can inhibit neutrophil elastase 18 and Kim et al have recently shown that coadministration of a neutrophil elastase inhibitor enhances the affinity and function of antibodies induced by alum as adjuvant 55 . In the same work, Kim et al showed that neutrophil elastase inhibitor supplementation can improve the efficacy of alum-adsorbed anti-SARS-CoV-2 vaccines by promoting the induction of IgA in the serum and mucosal secretions 55 .…”
Section: Discussionmentioning
confidence: 99%
“…U-Omp19 can inhibit neutrophil elastase 18 and Kim et al have recently shown that coadministration of a neutrophil elastase inhibitor enhances the affinity and function of antibodies induced by alum as adjuvant 55 . In the same work, Kim et al showed that neutrophil elastase inhibitor supplementation can improve the efficacy of alum-adsorbed anti-SARS-CoV-2 vaccines by promoting the induction of IgA in the serum and mucosal secretions 55 . Of note, U-Omp19 adjuvanted group presented the highest levels of RBD specific IgA in serum and BAL and the highest neutralizing activity against SARS-CoV-2 Spike-pseudotyped virions in BAL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has a higher affinity for uptake by DCs, which leads to an efficient delivery of antigens and an enhanced cross presentation. This results in strong humoral and cellular immune responses [19]. PAPE may provide potential insights into a safe and effective COVID-19 vaccine adjuvant platform.…”
Section: Aluminum-based Adjuvantsmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19) is an infectious disease caused by the pathogen of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In December 2019, the first known case was identified in Hubei Province, China [1].…”
Section: Introductionmentioning
confidence: 99%